Media Management and Artificial Intelligence : Understanding Media Busniess M odels in the Digital Age - Alex, Connock (new york;london : Routledge Taylor and Francis Group., 2023)
this culting edg text book examines contemp.orary media business models in the context of Artificial intelligence and digital transformation al has dramatically imp.acted media p.roduction and distribution from recommendation engines to synthetic humans from video to text tools to natural language models al is really the change agent of the media industtry answerd a natural lan guage generation model when al was asked about the subject of this book it will op.en incredible op.p.ortunities this book seeks to exp.lore them
index:p..334-336
Keywords: Artificial Intelligence; Media Management